Analisis Bahan Material Komponen Dan Pemanfaatan Hukum Termodinamika Dalam Desain Kulkas Yang Ramah Lingkungan - Dita Apriliyani; Hapyla Dharen; Binntang Akalla Junjunan; Muhammad Aswaeni Muldea (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
The issue of ozone depletion and surface global warming due to synthetic refrigerants has prompted educational laboratories employing cooling machines to seek environmentally friendly alternative refrigerants. Retrofitting involves replacing refrigerants (consumable substances serving as working fluids) with environmentally friendly alternatives. Refrigerators are essential household appliances that have a significant environmental impact. This paper addresses various aspects of environmentally friendly refrigerator design, encompassing the use of cutting-edge technology, routine maintenance, the utilization of waste heat, material recycling, and the selection of eco-friendly refrigerants. By focusing on energy efficiency and sustainable material usage, refrigerators can become more efficient and environmentally friendly. Through this comprehensive analysis, practical recommendations are emphasized for the eco-friendly use and maintenance of refrigerators.